SPRING EXERCISES AND TRAINING WALKING ON BEAMS BALANCE ON MOTION BALANCE BASIC STUDENT'S BODY - Indrayogi Indrayogi (Pendidikan Jasmani Universitas Siliwangi, 2021)
The background that underlies this research is the existence of several problems with the level of balance of movement of students which are low and very varied and there is no suitable method to train the balance of body movements. The purpose of this study was to determine the effect of stilts and balance beam exercises on the balance of body movements of elementary school students, and to know the difference between stilts training and walking exercises on balance blocks on the balance of body movements of elementary school students. In this study, the research object was elementary school students. The research method used in this research is the experimental research method. Then the measuring instrument used is the Modified Bass Test of Dynamic Balance. For data analysis using homogeneity test, normality test, hypothesis test and difference test. The hypothesis that the researcher proposes is that there is an effect of stilts and balance beam training on the balance of body movements and there are differences between the two. Based on the results of the research and discussion, it can be concluded that there is a difference in the effect of stilts training and walking on a balance beam on the balance of upper class students. This is based on the results of the calculation, the average difference in the improvement in the results of the stilts 4.0 and balance beam training results is 3.33.